1999
DOI: 10.1103/physrevb.60.13119
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between weak ferromagnetism and crystal symmetry inGd2CuO4-type cuprates

Abstract: Correlation between copper weak ferromagnetism ͑WF͒ and crystal structural symmetry of the Gd 2Ϫx M x CuO 4 ͑M ϭBi or Tb; 0рxр0.5͒ systems is reported. Detailed powder x-ray Rietveld refinement analysis on Gd 2Ϫx M x CuO 4 shows a systematic variation of oxygen distortion angle ␣͑Cu-O-Cu͒ with ionic size where the lattice layer mismatch lowers the crystal symmetry to an orthorhombic OЈ-phase with pseudotetragonal lattice parameter a 0 ϳb 0 ϳ5.508 Å. Weak ferromagnetic or canted antiferromagnetic order is the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…where w D (n) is determined by (5) or (6). The energy ( 8) and ( 7) were derived from (3) by ignoring the paraprocess and assuming weak total magnetization, |m| ≪ 1, implying |l| ≃ 1.…”
Section: B Simplified Model and Basic Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…where w D (n) is determined by (5) or (6). The energy ( 8) and ( 7) were derived from (3) by ignoring the paraprocess and assuming weak total magnetization, |m| ≪ 1, implying |l| ≃ 1.…”
Section: B Simplified Model and Basic Equationsmentioning
confidence: 99%
“…It influences appreciably the magnetic properties of several important classes of magnetic materials such as orthoferrites, manganites, some hightemperature superconducting cuprates, and others. 4,6 Another fundamental macroscopic manifestation of antisymmetric couplings (1) takes place in noncentrosymmetric magnetic crystals. Dzyaloshinskii showed that, in this case, the interaction (1) stabilizes long-periodic spatially modulated structures with fixed sense of rotation of the vectors S i .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DMI was first proposed in the 1950's for antiferromagnets such as α-Fe 2 O 3 to account for the existence of a weak ferromagnetism (Dzyaloshinskii, 1957;Moriya, 1960). In the following decades, several magnetic materials, such as spin glasses, orthoferrites, manganites or superconducting cuprates (Bogdanov et al, 2002;Coffey et al, 1991;Fert and Levy, 1980;Luo et al, 1999), were investigated for their noncollinear or helical magnetism and for the influence of DMI on the magnetic state. Theoretical models in non-collinear magnetism are often based on ab-initio calculations and density functional theory (Sandratskii, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For these materials, a correlation between weak ferromagnetism and the crystal symmetry has been discussed in detail. 30 We believe that such a correlation is also present in PFC and that the large canting observed in this compound is a direct result of its chiral lattice symmetry. Due to this symmetry, the orientation of the local easy axis varies by 90…”
Section: Magnetic Structurementioning
confidence: 97%